2002
DOI: 10.1211/0022357021778583
|View full text |Cite
|
Sign up to set email alerts
|

Omeprazole increases permeability across isolated rat gastric mucosa pre-treated with an acid secretagogue

Abstract: Triple therapy using proton-pump inhibitors (PPIs) in combination with oral antibiotics for the treatment of Helicobacter pylori-associated gastritis has shown increased efficacy for reasons that are still poorly understood. Possible explanations include a direct antibacterial effect of the PPIs or a PPI-mediated increase in bacterial susceptibility to antibiotics. Using an in-vitro model of rat gastric mucosa, we examined fluxes of a radiolabelled marker molecule through the interepithelial tight junctions un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 30 publications
(28 reference statements)
4
27
0
1
Order By: Relevance
“…These findings build on our earlier results showing that the PPI-induced gastric leak occurs in the corpus region of the stomach, allows only molecules of 4 kDa or smaller to permeate, is bidirectional, and depends on luminal acidification [2]. 3 H-digoxin flux experiments are very expensive to perform due to the high cost of radiolabeled drug and the very small amount of radioactivity which actually crosses the gastric barrier in the control as well as the omeprazoletreated states. This limited us to only four separate experiments.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…These findings build on our earlier results showing that the PPI-induced gastric leak occurs in the corpus region of the stomach, allows only molecules of 4 kDa or smaller to permeate, is bidirectional, and depends on luminal acidification [2]. 3 H-digoxin flux experiments are very expensive to perform due to the high cost of radiolabeled drug and the very small amount of radioactivity which actually crosses the gastric barrier in the control as well as the omeprazoletreated states. This limited us to only four separate experiments.…”
Section: Discussionsupporting
confidence: 74%
“…It has been established by our group and others that proton pump inhibitors (PPIs), as a class, are causing a transepithelial leak in the gastric corpus mucosa [1][2][3]. This leak is paracellular in nature, showing bidirectional symmetry.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent animal model studies, also by our group, showed the following properties of this leak: 1) it is bidirectional; 2) it allows molecules as large as 4,000 daltons to permeate, but not molecules 10,000 daltons or larger; 3) it manifests a similar dose dependence to that for inhibition of acid secretion; 4) it occurs near instantaneously if the proton pump inhibitor (PPI) concentration is sufficiently high; 5) it is a general property of PPIs and not specific to only one individual PPI; 6) it requires a luminal fluid pH below 5.0 [5]. These results confirm and extend the earlier findings of Hopkins et al (2002) [6] using rat gastric corpus, the first indication that omeprazole was inducing gastric transepithelial leak.…”
supporting
confidence: 84%
“…In previous studies with isolated rat gastric mucosa in vitro, omeprazole has been found to inhibit both basal acid secretion and acid output stimulated by either histamine or by dB-cAMP [2]. Although in a previous study with isolated rat gastric mucosa, histamine adequately stimulated acid secretion in the stomach tissue [6], in our studies, histamine was an ineffective secretagogue and dB-cAMP was used in all experiments.…”
Section: Acid Secretion Stimulationmentioning
confidence: 48%
“…One previous study has earlier reported an omeprazole-induced leak to 14 C-mannitol and a concomitant drop in transepithelial resistance in isolated rat gastric tissue stimulated with secretagogues [6].…”
Section: Introductionmentioning
confidence: 91%